Preventing Corruption in Prosecution Offices : Understanding and Managing for Integrity - Gramckow, Heike (World Bank, Washington, DC, 2014)
Considering the essential role of prosecutors in upholding the rule of law and pursuing government accountability, the integrity of prosecutorial operations is of special importance. At the same time, this critical role also exposes prosecutors to certain pressures and can make them vulnerable to corruption. This article outlines a range of special responses to detect, remedy, and prevent corruption within prosecution offices. While not entirely specific to prosecution agencies, the approaches outlined highlight the central importance of good management practices and a strong focus on preventing opportunities for corruption through effective policies and procedures, IT solutions, and transparent operations.